Greenwashing behaviours: causes, taxonomy and consequences based on a systematic literature review - Yang, Zhi; Nguyen, Thi Thu Huong; Nguyen, Hoang Nam; Nguyen, Thi Thuy Nga; Cao, Thi Thanh (Journal of Business Economics and Management, 2020)
This study used the systematic review methodology to examine peer-reviewed journal articles published in the Web of Science, ScienceDirect, Springer and Emerald Insight during the 2000–2020 period to analyse greenwashing. In an open market, the behaviours of state-owned enterprises (SOEs), private firms and multinational corporations (MNCs) pose an implicit greenwashing threat. Our focal point is to analyse corporate greenwashing in MNCs in host emerging markets, particularly in Asia, for two reasons. First, reports of greenwashing have increased around the world since Volkswagen was revealed to have falsified automobile emissions data. Second, MNCs play an important role in expanding market size and their behaviour is increasingly unpredictable. The analysis shows that MNCs tend to engage in greenwashing immediately after doing business in host emerging markets characterised by restricted regulations, clear market opportunities and low competitive pressure. When greenwashing occurs, it will harm the interests of not only consumers, but also society as a whole, despite offering significant benefits to existing stakeholders. In this case, the authorities should implement regulations to confront MNCs before attracting them, which should be enforced in practice.